Stepping motor vibration characteristics study - Leong, Winson Weng Chang. (2009)
In the automation industry, motors are used in many applications. Motors are range from standard AC motors for continuous operation application, to linear motion devices that convert rotational motion to linear motion, to stepping motors for precision positioning control. Stepping motor system allows for higher precision accuracy to transport load to the exact position. However, the automation industry is tremendously grown with more high speed and high precision applications. The vibration characteristic performance becomes the main concern of the stepping motor system. The vibration of the stepping motor will result the operation of not synchronous to the input command pulses and causing the motor to mis-step. A study will show the various vibration components that are present in the different ranges of speed. Finding on methodology in minimizing the vibration. One of the methodologies is micro-step drive and smooth-drive function. In the final stage, the result will show how effectively the micro-step drive and smooth-drive function to minimize the vibration during the stepping motor operation.